The current state of the organization of physical education in higher educational institutions of Ukraine and Poland - Banah, V. (Journal of Education, Health and Sport, 2016)
The study was aimed at identifying the general features and characteristics of the organization, content of physical education of students of higher educational institutions of Ukraineand the Republicof Poland. We have been used research methods: analysis, systematization, generalization. They had been used for processed in printed and electronic sources of information. The initial and final selection of such sources was based on keywords, their corresponding abbreviations, combinations, consideren the year of publication. We obtained data that showed a significant similarity in the forms of organization of physical education used in higher education institutions of both countries, but a significant difference in the number of hours for different types of physical activity of students and its content. One of the promising ways to improve the physical education of students - providing sports content and the use of various forms of organization of classes that is used in compulsory and institutional (at the choice of higher education) areas.